The cost- and income situation of the Hungarian pig breeding - Szili, Viktor (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The aim of my researches was to explore the present situation of Hungarian pig breeding sector using available financial and natural data. I have chosen two sectors for the elaboration of this analysis, the sow keeping and the pig fattening. For the comparison of the domestic situation with international data, I used the data of InterPIG, an international organization in the field of economics of pig breeding.I carried out my analyses based on the database of FADN (Farm Accountancy Data Network), which contains the data of roughly 80 000 agricultural enterprises in the 27 member states of the European Union, and which represents a population of 6.4 million farms. This database provides information about the structural, financial and accountancy data of farms by 150 different indicators of the different regions, sizes of farms and types of farming. In some countries – such as Hungary – the data are processed not only at farm level, but also on sectoral level. I have token consediration these sectoral datas in the most significant extent during my work.My analysis was based on FADN data and other data sources for the period between 2012 and 2014. I examined the changes of the key indicators for the cost-income analysis, I divided the sample into several segments, I explored the differences and also created some correlation coefficients. I hope that the article can help for the Hungarian farmers and the resarchers to see the domestic pig breeding situation more realistically, and reveals some break points for this sector.